Measles skin rash: Infection of lymphoid and myeloid cells in the dermis precedes viral dissemination to the epidermis - Laksono, Brigitta M.; Fortugno, Paola; Nijmeijer, Bernadien M.; de Vries, Rory D.; Cordisco, Sonia; Kuiken, Thijs; Geijtenbeek, Teunis B. H.; Duprex, W. Paul; Brancati, Francesco; de Swart, Rik L. (PLoS pathogens, 2020)
Measles is characterized by fever and a maculopapular skin rash, which is accompanied by immune clearance of measles virus (MV)-infected cells. Histopathological analyses of skin biopsies from humans and non-human primates (NHPs) with measles rash have identified MV-infected keratinocytes and mononuclear cells in the epidermis, around hair follicles and near sebaceous glands. Here, we address the pathogenesis of measles skin rash by combining data from experimentally infected NHPs, ex vivo infection of human skin sheets and in vitro infection of primary human keratinocytes. Analysis of NHP skin samples collected at different time points following MV inoculation demonstrated that infection in the skin precedes onset of rash by several days. MV infection was detected in lymphoid and myeloid cells in the dermis before dissemination to the epidermal leukocytes and keratinocytes. These data were in good concordance with ex vivo MV infections of human skin sheets, in which dermal cells were more targeted than the epidermal cells. To address viral dissemination to the epidermis and to determine whether the dissemination is receptor-dependent, we performed experimental infections of primary keratinocytes collected from healthy donors. These experiments demonstrated that MV infection of keratinocytes is mainly nectin-4-dependent, and differentiated keratinocytes, which express higher levels of nectin-4, are more susceptible to MV infection than proliferating keratinocytes. Based on these data, we propose a model to explain measles skin rash: migrating MV-infected lymphocytes initiate the infection of dermal skin-resident CD150+ immune cells. The infection is subsequently disseminated from the dermal papillae to nectin-4+ keratinocytes in the basal epidermis. Lateral spread of MV infection is observed in the superficial epidermis, most likely due to the higher level of nectin-4 expression on differentiated keratinocytes. Finally, MV-infected cells are cleared by infiltrating immune cells, causing hyperemia and edema, which give the appearance of morbilliform skin rash.